2015
DOI: 10.1039/c5ay01390a
|View full text |Cite
|
Sign up to set email alerts
|

A protocol for the quality assessment of illegally distributed human growth hormones with respect to identity, purity, endotoxin level and microorganism content

Abstract: Different methods based on MALDI-TOF-MS and double injection capillary zone electrophoresis (DICZE) were used for the identification and purity determination of somatropin in illegally distributed products.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
12
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
2
1

Relationship

3
0

Authors

Journals

citations
Cited by 3 publications
(12 citation statements)
references
References 27 publications
0
12
0
Order By: Relevance
“…It has been demonstrated that supra-physiological dosages can have fatal consequences [55]. Apart from the undesired consequences following the abuse of somatropin, our investigations have shown that the illegally marketed products contained high levels of impurities such as endotoxins [50]. Endotoxins are associated with Gram-negative bacteria which can cause severe immune response and diseases in humans [56,57].…”
Section: Identification Of Somatropin (Hgh)mentioning
confidence: 80%
See 3 more Smart Citations
“…It has been demonstrated that supra-physiological dosages can have fatal consequences [55]. Apart from the undesired consequences following the abuse of somatropin, our investigations have shown that the illegally marketed products contained high levels of impurities such as endotoxins [50]. Endotoxins are associated with Gram-negative bacteria which can cause severe immune response and diseases in humans [56,57].…”
Section: Identification Of Somatropin (Hgh)mentioning
confidence: 80%
“…The reaction is carried out at room temperature or at 37°C for 30 minutes up to 24 hours, depending on peptide or protein in question. It has been found that 30 minutes digestion of somatropin at room temperature generated enough tryptic fragments for the MALDI analyses [50]. For more complex proteins, such as human chorionic gonadotropin, the required time period for proteolysis is found to be 24 hours at 37°C.…”
Section: Proteolysismentioning
confidence: 99%
See 2 more Smart Citations
“…The migration time ratios varied between 0.997 and 1.005 (i.e., 1.001 ± 0.004), indicating good agreement between the observed and calculated migration times (Figure 2). It is to be noted that the use of capillary electrophoresis in combination with other techniques sharply enhances trueness of the identification [9].…”
Section: Resultsmentioning
confidence: 99%